Drive for Muscularity and Tendencies of Muscle Dysmorphia among Pakistani Bodybuilders: A Prevalence Study - Umaiza Bashir; Sadia Rehman; Fatima tu Zahra (Journal of the Pakistan Medical Association, 2021)
Objective: Preoccupation with a belief of insufficient muscularity affects mostly male gender throughout the world. Hence, it was necessary to study relationship between Drive for Muscularity and muscle dysmorphic tendencies in Pakistani culture. Method: A cross sectional research design was conducted on 211 participants (bodybuilders) in the age range early and middle adulthood (M= 26.25; SD= 5.946). Study was carried out in Lahore Pakistan in 2017 from June to September 2017. An indigenous Drive for Muscularity Inventory and Y-BOCS (BDD-YBOCS) administered to determine the drive for muscularity and tendencies of muscle dysmorphia. Results: The results indicated positive relationship between drive for muscularity and tendencies of muscle dysmorphia. Moreover, it revealed that 130 (62%) of the bodybuilders have a moderate level of drive for muscularity. Likewise, the unmarried bodybuilders with the age range of 18-25 years showed more drive for muscularity as compared to married bodybuilders with the age range of 26 and above (p< 0.001***). Conclusion: It was concluded that drive for muscularity and muscle dysmorphic tendencies are prevailing in Pakistani culture. Keywords: Drive for Muscularity, Tendencies of Muscle Dysmorphia, Continuous...